Minocycline attenuates subjective-rewarding effects of dextroamphetamine in humans - Sofuoglu, Mehmet (2010)
RATIONALE: Minocycline, a tetracycline antibiotic, interacts with brain glutamate and dopamine neurotransmission. In preclinical studies, minocycline attenuated amphetamine-induced acute dopamine release and subsequent behavioral sensitization. The goal of this study was to determine minocycline’s effects on the acute physiological, behavioral, and subjective responses to dextroamphetamine (DAMP) in healthy volunteers. METHODS: Ten healthy volunteers participated in an outpatient double-blind, placebo-controlled, crossover study. Subjects had a 5-day treatment period with either minocycline (200 mg/day) or placebo and then were crossed over for 5-days of the other treatment. After two days of taking the study medication, on days 3 and 4, subjects were randomly assigned to double-blind acute challenge with either 20 mg/70 kg DAMP or placebo DAMP (randomly labeled as drug A or B) and then crossed-over to the other challenge. On Day 5 (Experimental Session 3), subjects had the opportunity to self-administer either placebo or DAMP capsules by working on a progressive ratio computer task. RESULTS: Minocycline attenuated DAMP-induced subjective-rewarding effects but did not change DAMP choice behavior. Minocycline treatment speeded reaction times on a Go No-Go task and reduced plasma cortisol levels. CONCLUSIONS: These findings warrant further studies examining the potential use of minocycline for stimulant addiction.